2022
DOI: 10.1007/s10336-022-02018-8
|View full text |Cite
|
Sign up to set email alerts
|

Community engagement and data quality: best practices and lessons learned from a citizen science project on birdsong

Abstract: Citizen Science (CS) is a research approach that has become popular in recent years and offers innovative potential for dialect research in ornithology. As the scepticism about CS data is still widespread, we analysed the development of a 3-year CS project based on the song of the Common Nightingale (Luscinia megarhynchos) to share best practices and lessons learned. We focused on the data scope, individual engagement, spatial distribution and species misidentifications from recordings generated before (2018, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The demonstration of the ECS's reliability is important, as there is a negative stigma around citizen science data [25]. Our results are consistent with prior work that has shown that such data can be of a high quality [26][27][28]. The development and design of the tool likely contributed to its reliability.…”
Section: Discussionsupporting
confidence: 84%
“…The demonstration of the ECS's reliability is important, as there is a negative stigma around citizen science data [25]. Our results are consistent with prior work that has shown that such data can be of a high quality [26][27][28]. The development and design of the tool likely contributed to its reliability.…”
Section: Discussionsupporting
confidence: 84%
“…We believe that CS data on biodiversity, however, should not be seen as a substitute for academic biodiversity research, but rather as a valuable addition. Regarding the current quality debate, one must be aware of and accept the existing limitations of CS (Jäckel et al 2023). Recognition of CS data could and should yet be increased by establishing and communicating clear standards for data (quality), and encouraging collaboration between CS stakeholders and authorities.…”
Section: Discussionmentioning
confidence: 99%
“…Training to improve identification skills is expected to increase the data quantity and quality ( Greenwood, 2007 ; Bonney et al, 2009b ; McLaren & Cadman, 1999 ) and to improve the participants’ interest in the natural environment ( Hsu, Chang & Liu, 2019 ). System for automated birdsong recognition has been developed considerably (for example, Wood et al, 2022 ; Jäckel et al, 2023 ), and a library of sounds annotated by citizens will contribute to further improving accuracy of automated birdsong recognition.…”
Section: Introductionmentioning
confidence: 99%